Identification of prognostic genes in adrenocortical carcinoma microenvironment based on bioinformatic methods. (19th December 2019) - Li, Xiao; Gao, Yang; Xu, Zicheng; Zhang, Zheng; Zheng, Yuxiao; Qi, Feng
Abstract: Background: To identify prognostic genes which were associated with adrenocortical carcinoma (ACC) tumor microenvironment (TME). Methods and materials: Transcriptome profiles and clinical data of ACC samples were collected from The Cancer Genome Atlas (TCGA) database. We use ESTIMATE (estimation of stromal and Immune cells in malignant tumor tissues using expression data) algorithm to calculate immune scores, stromal scores and estimate scores. Heatmap and volcano plots were applied for differential analysis. Venn plots were used for intersect genes selection. We used protein‐protein interaction (PPI) networks and functional analysis to explore underlying pathways. After performing stepwise regression method and multivariate Cox analysis, we finally screened hub genes associated with ACC TME. We calculated risk scores (RS) for ACC cases based on multivariate Cox results and evaluated the prognostic value of RS shown by receiver operating characteristic curve (ROC). We investigated the association between hub genes with immune infiltrates supported by algorithm from online TIMER database. Results: Gene expression profiles and clinical data were downloaded from TCGA. Lower immune scores were observed in disease with distant metastasis (DM) and locoregional recurrence (LR) than other cases ( P  = .0204). Kaplan‐Meier analysis revealed that lower immune scores were significantly associated with poor overall survival (OS) ( P  = .0495). We screened 1649 differentially expressed genes (DEGs) and 1521 DEGs based on immune scores and stromal scores, respectively. Venn plots helped us find 1122 intersect genes. After analysing by cytoHubba from Cytoscape software, 18 hub genes were found. We calculated RS and ROC showed significantly predictive accuracy (area under curve (AUC) = 0.887). ACC patients with higher RS had worse survival outcomes ( P  < .0001). Results from TIMER (tumor immune estimation resource) database revealed that HLA‐DOA was significantly related with immune cells infiltration. Conclusion: We screened a list of TME‐related genes which predict poor survival outcomes in ACC patients from TCGA database. Abstract : To identify prognostic genes in adrenocortical carcinoma (ACC) tumor microenvironment (TME).